Presumptive Taxation in Sub-Saharan Africa : Experiences and Prospects - Tadesse, Helaway (IMF Working Papers; Working Paper ;, 1996)
Considering the need to broaden the tax base and to increase tax revenue in an efficient, equitable, and cost-effective manner, this paper analyzes presumptive taxation methods and their application in sub-Saharan Africa. Presumptive taxation involves simple techniques to capture income that frequently escapes conventional taxation. Presumptive taxation methods could be used more intensively in sub-Saharan Africa, and presumptive taxes on imports, withholding schemes, and graduated business license fees are most effective in raising additional tax revenue in a way commensurate with efficiency, equity, and administrative expediency. Also, intensified presumptive taxation will need stronger institutional capacity in tax administration.